Demand-Driven Youth Training Programs : Experimental Evidence from Mongolia - Alzua Soyolmaa Batbekh, Maria Laura; Batchuluun, Altantsetseg; Dalkhjav, Bayarmaa; Galdo, Jose (World Bank, Washington, DC, 2020)
The effectiveness of a demand-driven vocational-training program for disadvantaged youth in Ulaanbaatar, the capital city of Mongolia is assessed through a randomized controlled trial. Mongolia, a transitional country whose economic structure shifted from a Communist, centrally planned economy to a free-market economy over a relatively short period, offers a new setting in which to test the effectiveness of market-based active-labor-market policies. Results show short-term positive impacts on self-employment and skills match, while positive but uncertain effects emerge for employment and earnings. Substantial heterogeneity emerges as relatively older, richer, and better-educated individuals drive these positive effects. A second intervention, in which participants were randomly assigned to receive newsletters with information on market returns to vocational training, shows statistically meaningful effects on the length of exposure to the program (i.e., number of training days attended). These positive impacts, however, do not lead to higher employment or greater earnings.